(untitled) (Research, Society and Development, 2022)
To describe the distribution pattern of the stomach cancer mortality rate in Brazil and its regions, according to sex, between the year 2011 and 2015. Mortality values were described by the DATASUS atlas mortality and stratified by sex in the year 2011 and 2015 and analyzed by the Two-Way Anova test. It was observed that there was a higher mortality incidence in the Southeast and lower in the Midwest for both sexes. The Northeastern region presented a high number of cases standing out in relation to the North, Center-west and South regions (P <0.05). Regarding the incidence of male mortality, the North and Northeast regions showed continuous growth over the 5 years studied in this study. On the other hand, the Central-West, South and Southeast regions showed small variations, with 2013 being the most affected in the Midwest and Southeast and 2012 in the South. However, these variations were not significant in terms of statistical test. It is important to know these mortality rates in the regions to identify and define priority regions for early interventions that increase survival and reduce mortality in these populations.